The Bronsted acidity of three- and two-dimensional zeolites - Thang, Ho Viet; Vaculík, Jan; Prech, Jan; Kubu, Martin; Cejka, Jiri; Nachtigall, Petr; Bulánek, Roman; Grajciar, Lukas (Elsevier Science BV, 2019)
The zeolite activity in processes driven by Bronsted acid sites is determined by the distribution of the protons in the zeolite and strength of their interaction with the framework. This study aims to assess how much the transformation from three-dimensional (3D) bulk zeolite to its corresponding two-dimensional (2D) layered form changes the proton distribution and strength of the proton-framework interaction and thus how much it affects the zeolite Bronsted acid strength. Zeolites with three distinct topologies, MWW, PCR, and MFI, which form also layered analogues with considerably different thickness and silanol density were considered. To probe the Bronsted acidity of both 3D and 2D forms, an array of typical acidity descriptors (i.e., O-H stretching frequency, shift of O-H frequencies upon adsorption of CO probe molecule, C-O stretching frequencies and adsorption enthalpies of the CO adsorption complex) have been evaluated, employing both dispersion-corrected density functional theory and Fourier-transform infrared spectroscopy. Using these descriptors, the Bronsted acidity of 2D form is, on average, the same or just slightly lower than that of the 3D form. Transformation to layered form does affect the proton distribution and values of acidity descriptors for individual T sites, however, if all T sites are considered, the aggregate effect is almost negligible. Hence, these results suggest that a larger effect of the 3D - > 2D transformation can be expected for frameworks with fewer distinct T sites.
Bronstedova kyselost tří- a dvou-dimenzionálních zeolitů
Keywords: Bronsted acidity; zeolite; OH stretching frequency; CO stretching frequency; Adsorption; Fourier-transform infrared spectroscopy; Density functional theory; Bronstedova kyselost; zeolit; adsorpce; FTIR; DFT